PENYULUHAN PENYAKIT TIDAK MENULAR (PTM) UNTUK MENUMBUHKAN KESADARAN REMAJA - Rose, S.; Shofiyyatunnisaak, N.A.; Amrullah, A.W. (Buletin Udayana Mengabdi, 2024)
Non-Communicable Diseases (PTM) cannot be transmitted to other people and develop slowly over a period of time. This phenomenon has spread to teenagers, with not a few cases of death. This must be addressed immediately by increasing knowledge and vigilance, especially among adolescents. This activity was carried out for students of SMK Marsudirini Marganingsih Surakarta. Beginning with the provision of a pre-test and then providing learning materials related to PTM, continuing with a question and answer discussion, and filling out the post-test as an indicator of the success of this activity. The main target of this activity is all students. While the participants who attended this activity were 67 people, including students (76.1%), teachers (20.9%), and employees (3%), As many as 34 students who filled out the pretest and posttest questionnaires found that there was an increase in knowledge, even though the average rating was still in the low category. It is hoped that this increase can be used as information for strengthening knowledge and awareness about NCDs, increasing awareness in adolescents regarding the risk of NCDs, and preventing nutritional problems, especially in adolescents with NCDs.